The Role of Aisyiyah's Thought in the Advancement of Early Childhood Education in Kendal District - Rachmawati, Dian; Masduki, Yusron; Mahmudah, Fitri Nur (Ridwan Institute, 2023)
This study aims to analyze the role of Aisyiyah in the development of education in Kendal Regency in 1950-2020, so as to find out the background of the establishment of Aisyiyah Kendal. Aisyiyah as a special autonomy organization of Muhammadiyah can nurture women to be educated to become leaders, and be prepared to become administrators in the Muhammadiyah women's organization. Aisyiyah's presence in developing her educational role in Kendal Regency has given birth to strong cadres in organization. Aisyiyah's presence in Kendal is inseparable from the arrival of Muhammadiyah ideas and thoughts. Aisyiyah is engaged in social, educational, health and religious domains, this research uses historical methods consisting of heuristics, verification, interpretation, historiography. Aisyiyah has activities with several programs, one of which is in the field of education, especially in Bustanul Athfal Kindergarten (TK), Aisyiyah program on worship guided by the Central Leadership (PP) in Jakarta about Kemuhammadiyahan and Keaisyiyahan.